Representações de pessoas com transtorno mental sobre as infecções sexualmente transmissíveis e o HIV/Aids - Adriana da Silva Gomes (2010)
Patients with severe mental illness are more vulnerable to sexually transmitted infections STIs,and HIV/AIDS, diseases that have a big impact on public health nowadays. Creating a linkbetween these subjects and the diseases allows for the (re)construction of their representationsabout the latter, expressed in attitudes, words, and actions, in their relationships with others. Theaim of this study was to understand the representations patients with severe mental illness havein relation to HIV/AIDS and other STIs, comparing them to those of other population groupsavailable in the literature. In order to reach said objective, we used a qualitatice methodology,with theoretical-methodological orientation based on Social Representation Theory. The researchwas carried out at two psychiatric hospitals in Minas Gerais, at two Psychosocial Attention inMinas Gerais and in Rio de Janeiro, Brazil. We interviewed 39 people followed at theabovementioned services, who were not in a crisis and who understood and accepted taking partin the study. They were interviewed individually, answering open-ended and in-depth questions.The answer analysis was based on Structural Analysis of Narrative. The results were divided intothree categories: 1/Representations of STIs and AIDS; 2/Representations about transmissibilityand prevention of STIs and HIV/AIDS; and 3/Representations about risk and preventiveeducation on STIs and HIV/AIDS. Data interpretation revealed that representation of STIs are ofdiseases transmitted through sex, that are dangerous, related to dirtiness, that can be seen inthe way people walk. No distinction is made between HIV and AIDS, and the representationsare the same found for other STIs, that the disease kills, causes shame and fear; and can leadto prejudice. For prevention, condoms are listed as important, but its use is close to none,because it is possible to prevent catching the disease by not having sexual intercourse withpeople you dont know and well as women who work in the streets. Men and womenconsider the former more forward, but men also consider themselves smarter andinvulnerable, whereas women who have been or are sexually active feel more at risk of infectionbecause they have less room for negotiation in relation to condoms. In general, thus,representations are the same found in other population groups, but the social and culturalvulnerability, access to school is rare and mental health services is increased by situationsspecific to the clinical picture; by a powerful feeling of invulnerability when facing life ingeneral; moreover, there are many occurrences of sexual abuse for both genders, by thedifficulties in maintaining stable relationships, by paid and unsafe sex without the use ofcondoms. In addition to these aspects of social vulnerability, access to school is low and mentalhealth services do not have educational activities on sexual health as common practice, thusmaking life experiences, friends and television the main source for the construction ofrepresentations. Articulating public policies, social and health services, and making availableprofessionals who can carry out sexual education actions and follow up, with the specificaudience of people with mental disabilities, as well as the effective protections of those in asituation of destitution, is essential for an integral assistance.